Bruton’s Tyrosine Kinase-Mediated Signaling in Myeloid Cells Is Required for Protective Innate Immunity During Pneumococcal Pneumonia - de Porto, Alexander P.; Liu, Zhe; de Beer, Regina; Florquin, Sandrine; Roelofs, Joris J. T. H.; de Boer, Onno J.; den Haan, Joke M. M.; Hendriks, Rudi W.; van ‘t Veer, Cornelis; van der Poll, Tom; de Vos, Alex F. (Frontiers in Immunology, 2021)
Bruton’s tyrosine kinase (Btk) is a cytoplasmic kinase expressed in B cells and myeloid cells. It is essential for B cell development and natural antibody-mediated host defense against bacteria in humans and mice, but little is known about the role of Btk in innate host defense in vivo. Previous studies have indicated that lack of (natural) antibodies is paramount for impaired host defense against Streptococcus (S.) pneumoniae in patients and mice with a deficiency in functional Btk. In the present study, we re-examined the role of Btk in B cells and myeloid cells during pneumococcal pneumonia and sepsis in mice. The antibacterial defense of Btk-/- mice was severely impaired during pneumococcal pneumosepsis and restoration of natural antibody production in Btk-/- mice by transgenic expression of Btk specifically in B cells did not suffice to protect against infection. Btk-/- mice with reinforced Btk expression in MhcII+ cells, including B cells, dendritic cells and macrophages, showed improved antibacterial defense as compared to Btk-/- mice. Bacterial outgrowth in Lysmcre-Btkfl/Y mice was unaltered despite a reduced capacity of Btk-deficient alveolar macrophages to respond to pneumococci. Mrp8cre-Btkfl/Y mice with a neutrophil specific paucity in Btk expression, however, demonstrated impaired antibacterial defense. Neutrophils of Mrp8cre-Btkfl/Y mice displayed reduced release of granule content after pulmonary installation of lipoteichoic acid, a gram-positive bacterial cell wall component relevant for pneumococci. Moreover, Btk deficient neutrophils showed impaired degranulation and phagocytosis upon incubation with pneumococci ex vivo. Taken together, the results of our study indicate that besides regulating B cell-mediated immunity, Btk is critical for regulation of myeloid cell-mediated, and particularly neutrophil-mediated, innate host defense against S. pneumoniae in vivo.